STRUKTUR DAN POLA KEPEMIMPINAN KYAI DALAM PESANTREN DI JAWA - Fadhilah, Amir (Hunafa: Jurnal Studia Islamika, 2011)
Abstract: The world of pesantren and the Islamic clerics’  charisma  is one of the interesting phenomena to be studied. The style of clerics’ life and religious students  is so great that it makes Islamic boarding  school posess a multi-dimensional  function: The Kyais not only are not only required as priests in religious  ceremonies  and rituals , but also often  required her presence  to  resolve  the case or the difficulties  that  befall  the community. In this context,  the role of the Islamic clerics  is increasingly rooted  in the community when their presences  are believed  to bring fortune. The existence of  structures  and patterns of  authority  (leadership) clerics  in the Islamic  world  remain  sustainable,  because  the Islamic clerics  have  internal social nets  (among  the religious schools)  and   external  social netwoeks (with  the world   outside  pesantren),  includes  genealogical  network,  ideological network,  intellectual  network, theological  network, and spiritual network.Kata Kunci: pola kepemimpinan kyai, pesantren, kharismatik dan jaringan